Correction with oral hydration improves maternal and perinatal outcome in women with third trimester isolated oligohydramnios - Aggarwal, Pragati; Patra, Sharda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Oligohydramnios is related to serious maternal and fetal complications. In case of isolated oligohydramnios in third trimester maternal oral hydration has shown promising results in improving maternal and perinatal outcome. Methods: This study was conducted on 50 pregnant women complicated by idiopathic oligohydramnios (AFI<5) in third trimester. Their pre hydration daily fluid intake was noted and they were advised to take oral fluids more than their usual intake (according to their convenience). The daily fluid intake and AFI was measured on day1, day2, day3 then weekly till delivery. At delivery maternal and fetal outcome were measured. Results: The mean AFI of the study population at the time of enrolment was 4.25±1.01 and daily mean fluid intake was 1.46±0.41. The post hydration fluid intake per day was significantly high as compared to pre hydration fluid intake (4.40±0.51 litres vs 1.46±0.41 litres, p<0.001). A significant difference in the amniotic fluid index was seen post hydration. The mean AFI on day 1, day 2, day 3 was 6.19±0.93, 7.33±1.13, 8.0±1.07 as compared to pre hydration AFI 4.25±1.01 (p<0.001). The amniotic fluid index post hydration normalized (AFI>8) in 6%, 30%, 61% and 100% of women on day1, day2, day3 and after a week. The perinatal outcome was favourable in all the women with 100% live births and a mean birth weight of 2.77±0.29 kg. Conclusions: A simple correction of maternal dehydration by an adequate and sustained daily oral fluid intake in pregnancies complicated by isolated third oligohydramnios in third trimester significantly improves amniotic fluid index, maternal outcome and perinatal outcome.